2018
DOI: 10.18590/euscorpius.2018.vol2018.iss271.1
|View full text |Cite
|
Sign up to set email alerts
|

Scorpions of the Horn of Africa (Arachnida, Scorpiones). Part XVII.Revision of Neobuthus, with description of seven new species from Ethiopia, Kenya and Somaliland (Buthidae)

Abstract: Euscorpius is the first research publication completely devoted to scorpions (Arachnida: Scorpiones). Euscorpius takes advantage of the rapidly evolving medium of quick online publication, at the same time maintaining high research standards for the burgeoning field of scorpion science (scorpiology). Euscorpius is an expedient and viable medium for the publication of serious papers in scorpiology, including (but not limited to): systematics, evolution, ecology, biogeography, and general biology of scorpions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 810 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…n. from all other species of the genus. According to the characters used in the key published in Kovařík et al (2018), the new species is most similar to N. gubanensis Kovařík et al, 2018, which is also confirmed by DNA phylogeny (paper in preparation). Morphologically, it is difficult to distinguish these two species based on single specimens but we can see that female of N. solegladi sp.…”
Section: Neobuthus Awashensissupporting
confidence: 55%
See 4 more Smart Citations
“…n. from all other species of the genus. According to the characters used in the key published in Kovařík et al (2018), the new species is most similar to N. gubanensis Kovařík et al, 2018, which is also confirmed by DNA phylogeny (paper in preparation). Morphologically, it is difficult to distinguish these two species based on single specimens but we can see that female of N. solegladi sp.…”
Section: Neobuthus Awashensissupporting
confidence: 55%
“…n. from all other species of the genus. According to the characters used in the key published in Kovařík et al (2018), the new species is most similar to N. amoudensis Kovařík et al, 2018 and N. gubanensis Kovařík et al, 2018, which is also confirmed by DNA phylogeny (paper in preparation). All examined specimens of N. amoudensis have pedipalp movable finger with 6 subrows of denticles (figs.…”
Section: Neobuthus Awashensismentioning
confidence: 52%
See 3 more Smart Citations